Opposing Age-Related Trends in Absolute and Relative Risk of Adverse Health Outcomes Associated With Out-of-Office Blood Pressure - Yan Li; Lutgarde Thijs; Zhen-Yu Zhang; Kei Asayama; Tine W. Hansen; José Boggia; Kristina Björklund-Bodegård; Wen-Yi Yang; Teemu J. Niiranen; Angeliki Ntineri; Fang-Fei Wei; Masahiro Kikuya; et al. (LIPPINCOTT WILLIAMS & WILKINS, 2022)
Participant-level meta-analyses assessed the age-specific relevance of office blood pressure to cardiovascular complications, but this information is lacking for out-of-office blood pressure. At baseline, daytime ambulatory (n=12 624) or home (n=5297) blood pressure were measured in 17 921 participants (51.3% women; mean age, 54.2 years) from 17 population cohorts. Subsequently, mortality and cardiovascular events were recorded. Using multivariable Cox regression, floating absolute risk was computed across 4 age bands (<= 60, 61-70, 71-80, and >80 years). Over 236 491 person-years, 3855 people died and 2942 cardiovascular events occurred. From levels as low as 110/65 mm Hg, risk log-linearly increased with higher out-of-office systolic/diastolic blood pressure. From the youngest to the oldest age group, rates expressed per 1000 person-years increased (P<0.001) from 4.4 (95% CI, 4.0-4.7) to 86.3 (76.1-96.5) for all-cause mortality and from 4.1 (3.9-4.6) to 59.8 (51.0-68.7) for cardiovascular events, whereas hazard ratios per 20-mm Hg increment in systolic out-of-office blood pressure decreased (P <= 0.0033) from 1.42 (1.19-1.69) to 1.09 (1.05-1.12) and from 1.70 (1.51-1.92) to 1.12 (1.07-1.17), respectively. These age-related trends were similar for out-of-office diastolic pressure and were generally consistent in both sexes and across ethnicities. In conclusion, adverse outcomes were directly associated with out-of-office blood pressure in adults. At young age, the absolute risk associated with out-of-office blood pressure was low, but relative risk high, whereas with advancing age relative risk decreased and absolute risk increased. These observations highlight the need of a lifecourse approach for the management of hypertension.